ADDRESS SYSTEM OF GAYONESE LUT AND DERET IN BENER MERIAH - Cut Kemala Sari; Zainuddin . .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
ABSTRACTThis study deals with Address System in one ethnic namely Gayonese Lut and Deret in Bener Meriah. The objective of this study is to describe the functions of address system Gayonese Lut and Deret in Bener Meriah. This study applied qualitative descriptive method. The techniques for collecting data were through giving the questionnaire sheets to the twelve subjects and record the conversation of interview with subjects and also the informants by taking the video directly. The result of this study found that Gayonese Lut has five functions address system namely Attract people attention (5.71), Show intimacy (28.58), Show politeness (7.14), Show power differential (20.00), and Reflect identity (38.57).  Gayonese Deret also has five functions of address system namely Attract people attention (10.00), Show intimacy (20.00), Show politeness (32.00), Show power differential (14.00), and Reflect identity (24.00). In Gayonese Lut, Reflect identity is the most function of address system while in Gayonese Deret is Show politeness. Keywords: Address System, Gayonese, Lut, Deret.